2018
DOI: 10.1515/tnsci-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium protects in episodes of critical perfusion after aneurysmal SAH

Abstract: BackgroundTo analyze whether magnesium has a neuroprotective effect during episodes that indicate a critical brain perfusion after aneurysmal subarachnoid hemorrhage (SAH).Methods107 patients with aSAH were randomized to continuously receive intravenous magnesium sulfate with target serum levels of 2.0 – 2.5 mmol/l (n = 54) or isotonic saline (n = 53). Neurological examination and transcranial Doppler sonography (TCD) were performed daily, Perfusion-CT (PCT) was acquired in 3-day intervals, angiography in case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Although neurological involvement is a quite common feature in GS, to date no one has demonstrated the presence of EMG alterations. We postulate that hypomagnesemia may impair the normal nerve trophism, since the importance of Mg2+ in neuroprotection is well described (15). Finally, we reported a GS with a novel SCL12A3 variation: to our knowledge, this is the very first heterozygous mutation in exon 23 (2738G>A), because the only other case of mutation involving exon 23, described in a Chinese case report, was homozygous and its nucleotide change was 2744 G>A (1).…”
Section: Case Reportmentioning
confidence: 86%
“…Although neurological involvement is a quite common feature in GS, to date no one has demonstrated the presence of EMG alterations. We postulate that hypomagnesemia may impair the normal nerve trophism, since the importance of Mg2+ in neuroprotection is well described (15). Finally, we reported a GS with a novel SCL12A3 variation: to our knowledge, this is the very first heterozygous mutation in exon 23 (2738G>A), because the only other case of mutation involving exon 23, described in a Chinese case report, was homozygous and its nucleotide change was 2744 G>A (1).…”
Section: Case Reportmentioning
confidence: 86%
“…For a more detailed description of our institutional management of aSAH patients, we refer to our previous works [ 14 , 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our institution, we have studied the effects of magnesium sulfate in aSAH patients extensively in experimental as well as in clinical studies [ 14 , 18 , 19 ]. Unlike several multicentric studies that administered magnesium in a fixed-dose manner and failed to find beneficial effects [ 20 ], a randomized controlled trial in our institution demonstrated the effectiveness of a tailored magnesium therapy guided by serum concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Target values are maintained using isotonic fluid infusion, packed red blood cells, and norepinephrine. All patients receive continuous intravenous magnesium for neuroprotection, vasospasm, and DCI prophylaxis with a target serum concentration of 2-2.5 mmol/L for the first 14 days following aSAH [16][17][18].…”
Section: Institutional Standard Management Of Asah Patientsmentioning
confidence: 99%